Estimating an Equilibrium Exchange Rate for the Argentine Peso - Coppola, Andrea (World Bank, Washington, DC, 2016)
This paper assesses the equilibrium value of the Argentine peso exchange rate based on the country's economic fundamentals and compares it with the official exchange rate value. The paper estimates a behavioral equilibrium exchange rate model that allows for movements in the equilibrium real effective exchange rate based on changing economic fundamentals, using monthly data from 1980 to 2015. The analysis identifies four key fundamentals driving the equilibrium exchange rate in Argentina: terms of trade, productivity differentials, foreign currency reserves, and trade openness. Based on these fundamentals, before the exchange rate reunification that took place at the end of 2015, the Argentine peso was overvalued by 39 percent. The results are robust to alternative estimation approaches.